SDG-Based Learning Through the Teaching Assistance Program at SMP 4 Polokarto (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program was conducted to address low student engagement and the limited integration of sustainability values in classroom learning at SMP Negeri 4 Polokarto. The program aimed to improve student engagement and learning outcomes through Sustainable Development Goals (SDGs)-based teaching assistance. A participatory approach was employed by involving university students as teaching assistants who collaborated with teachers in implementing interactive and contextual learning activities. The program was conducted from Agustus 2025 to January 2026 and included classroom teaching assistance, anti-bullying socialization, healthy exercise activities, and waste recycling activities. Data were collected through pretests, posttests, and observations, while learning outcomes were analyzed using percentage gain from pretest and posttest scores. The results showed that students’ learning outcomes increased in all classes, with percentage gains ranging from 33% to 78%. Student engagement also improved through more active participation, better classroom interaction, and higher learning motivation during learning activities. In addition, the supporting programs strengthened students’ social awareness, physical readiness, and environmental responsibility. Overall, SDGs-based teaching assistance created a more meaningful, contextual, and student-centered learning environment.
Keywords: Teaching Assistance; Learning Outcomes; Student Engagement; SDGs.